Study Discipline Among High School Students: Effects of Social Media Usage, Self-Management, and Peer Environment - Desi Luty Ermawati Natonis; Yeheskial Nggandung; Agustina Butar-Butar (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Poor study discipline among students remains a significant educational concern that may negatively affect academic achievement. This study aims to examine the effects of social media usage intensity, self-management, and peer environment on students’ study discipline. A quantitative approach using an ex post facto research design was employed. The participants were 150 students from State Senior High School No. 7 Kupang, selected through purposive sampling. Data were collected using a structured questionnaire with a four-point Likert scale and analysed using multiple linear regression with SPSS. The findings indicate that social media usage intensity has a significant negative effect on students’ study discipline, whereas self-management has a significant positive effect. In contrast, peer environment shows a significant negative effect on study discipline. Simultaneously, the three independent variables significantly influence students’ study discipline (F = 57.640, p < 0.001). The coefficient of determination (R² = 0.542) indicates that 54.2% of the variance in students’ study discipline is explained by social media usage intensity, self-management, and peer environment. In comparison, the remaining 45.8% is influenced by other factors outside the model. These findings support the application of Social Cognitive Theory by highlighting the interaction between personal and environmental factors in shaping students’ study discipline. The study suggests that strengthening self-management, promoting responsible social media use, and fostering supportive peer environments may help improve students’ study discipline.